A novel quinazolinone chalcone derivative induces mitochondrial dependent apoptosis and inhibits PI3K/Akt/mTOR signaling pathway in human colon cancer HCT-116 cells. (January 2016) - Wani, Zahoor Ahmad; Guru, Santosh Kumar; Rao, A.V. Subba; Sharma, Sonia; Mahajan, Girish; Behl, Akanksha; Kumar, Ashok; Sharma, P.R.; Kamal, Ahmed; Bhushan, Shashi; Mondhe, Dilip M.
Abstract: We have synthesized a novel quinazolinone chalcone derivative (QC) and first time reported its in-vitro and in-vivo anticancer potential. It inhibited the cell proliferation of different cancer cell lines like PC-3, Panc-1, Mia-Paca-2, A549, MCF-7 and HCT-116. It induces apoptosis as measured by several biological endpoints such as apoptotic body formation, evident by Hoechst and scanning electron microscopy, enhanced annexinV-FITC binding of the cells, increased sub-G0 cell fraction, loss of mitochondrial membrane potential (Δψm), reduction of Bcl-2/Bax ratio, activation of caspase-9, caspase-3 and PARP-1 (poly-ADP Ribose polymerase) cleavage in HCT-116 cells. In spite of apoptosis, QC significantly hammers the downstream and upstream signaling cascade of PI3K/Akt/mTOR pathway and cell cycle regulator Skp-2, p21 and p27. Interestingly, QC induces the S and G2/M phase of HCT-116 cells at experimental doses. QC inhibits the tumor growth of Ehrlich ascites carcinoma (EAC), Ehrlich tumor (ET, solid) and sarcoma-180(solid) mice models. Furthermore, it was found to be non-toxic as no animal mortality (0/7) occurred during experimental doses. The present study provides an insight of anticancer potential of QC, which may be useful in managing and treating cancer. Graphical abstract: Highlights: We have synthesized a novel quinazolinone-chalcone derivative, QC. It inhibits PI3K/Akt/mTOR pathway. It induces mitochondrial dependant apoptosis. It inhibits the growth of EAC, EAT and Sarcoma-180 tumors without any side effects.